2010
DOI: 10.1016/j.expneurol.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia reduces neurokinin-1 (NK1) receptor density in small dendrites of non-catecholaminergic neurons in mouse nucleus tractus solitarius

Abstract: Chronic intermittent hypoxia (CIH) is a frequent concomitant of sleep apnea, which can increase sympathetic nerve activity through mechanisms involving chemoreceptor inputs to the commissural nucleus of the solitary tract (cNTS). These chemosensory inputs co-store glutamate and substance P (SP), an endogenous ligand for neurokinin-1 (NK 1 ) receptors. Acute hypoxia results in internalization of NK 1 receptors, suggesting that CIH also may affect the subcellular distribution of NK 1 receptors in subpopulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
(104 reference statements)
0
13
1
Order By: Relevance
“…We identified mature synapses on serial sections and defined them as described previously (31). Details are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…We identified mature synapses on serial sections and defined them as described previously (31). Details are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…SP and the NK1R have been shown to play an integral role in the modulation of homeostatic function in the medulla, including regulation of respiratory rhythm generation [ 14 16 ], integration of cardiovascular control [ 17 ], modulation of the baroreceptor reflex [ 18 ] and mediation of the chemoreceptor reflex in response to hypoxia [ 19 , 20 , 28 ]. In this study, we observed abnormalities related to development and sex in NK1R binding within multiple nuclei of the medullary homeostatic network in SIDS cases incuding absolute reductions in binding in the NTS and and all sub-divisions of IO nuclei (PIO, MAO, DAO).…”
Section: Discussionmentioning
confidence: 99%
“…The NTS houses the primary relay station for brainstem transmission of important respiratory and cardiovascular reflexes and is enriched with a high density of SP containing axon terminals [ 29 , 30 ]. Evidence from animal studies indicates a functional role for SP in the NTS as a central integrator of cardiovascular control [ 17 ], modulator of baroreceptor reflex sensitivity [ 18 ] and a primary excitatory mediator of the chemoreceptor reflex in response to hypoxia [ 19 , 20 ]. In rodent models, activation of NK1R by SP in the NTS stimulates respiration, while loss of NK1R reduces the respiratory response, severely impairing the chemoreceptor reflex and selective lesion of NK1R expressing neurons in the NTS blunts cardiovascular reflexes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, receptor down regulation due to desensitization could lead to decreased excitatory effects of substance P on respiration. Lastly, exposure to chronic intermittent hypoxia causes a decrease in NK1 receptor density on NTS neurons [34] . However, it has not been shown how chronic intermittent hypoxia affects the chemosensitive response of NTS neurons or whether chronic hypoxia affects NK1 receptor density on NTS neurons.…”
Section: Introductionmentioning
confidence: 99%